Virtual Reality in Forensic Investigation: Exploring Applications and Advancements - Aditya Kumar; Vinny Sharma; Sudhir Kumar; Arvind Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
At the present time, there is a growing body of scholarly study focused on the development of virtual worlds and scenarios that have the potential to provide entirely sensory-rich alternative adventures that incorporate tangible, visual, and audio aspects. Once implemented properly, these kinds of efforts have the potential to be quite effective. Through a comprehensive analysis of realistic virtual reality and its technological ingredients, the present investigation intends to investigate appropriate approaches for effectively recreating virtual crime scenes. In the area of forensic examination, the re-enactment of the scene of an incident is a crucial procedure that helps determine the order in which events occurred. Enhancing comprehension and achieving straightforward, high-quality monitoring are the main goals of legal criminal investigation documentation. However, traditional methods are not adequate regarding it thorough recreation for entire scene of crime. The incorporation of methods for visualising information in multiple dimensions facilitates the thorough analysis of various types of proof gathered at the scene of crime, hence aiding in the development of a cohesive story. Rather of being displayed on traditional computer screens, the content is delivered via immersive virtual reality (VR). A thorough recreation of a crime scene is made possible by the links between different evidence chains. This is achieved by the application of forensic tools and specialist knowledge to examine the sources of harm and identify those who may be at fault. When multidimensional imaging techniques are used to many kinds of criminal situations, it becomes possible to conduct a more thorough investigation and perform a range of insightful analyses, including accurate measurement